2011
DOI: 10.1097/bcr.0b013e318217f954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Burn Injury: Preliminary Results From Prospective Study

Abstract: Reducing diabetes mellitus complications has been a major focus for Healthy People 2010. A prior retrospective cohort of our burn center's admissions revealed worse outcomes among diabetic patients, that is, increased infection rates, grafting and graft complications, and increased length of hospital stay. Therefore, a prospective study has been designed to carefully assess wound repair and recovery of diabetic and nondiabetic burn patients. Our long-term aim is to determine the characteristics of the wound mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 16 publications
4
19
0
Order By: Relevance
“…However, despite the increased risk of HAIs, no difference in the risk of inpatient mortality was seen. Our findings support previous research which found that DM increased the average length of stay and the incidence of complications (which include infections) [2023]. …”
Section: Discussionsupporting
confidence: 92%
“…However, despite the increased risk of HAIs, no difference in the risk of inpatient mortality was seen. Our findings support previous research which found that DM increased the average length of stay and the incidence of complications (which include infections) [2023]. …”
Section: Discussionsupporting
confidence: 92%
“…7,10 Hence, graft take rates compared with relatively healthy patients are distinctly lower. 8,10,11 In our patients, we could confirm that punctual bleeding after tangential excision was not very significant. Nevertheless, split-skin take was rather high when using TNP.…”
Section: Discussionsupporting
confidence: 73%
“…10 Therefore, diabetic patients with foot burns show a high rate of amputations. 8,9,11 It is known that topical negative pressure (TNP) dressings alias negative pressure wound therapy can increase graft take rate, even in burned patients. 12,13 However, the effectiveness of TNP on grafts in diabetic patients with foot scalds has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemic conditions induce various manifestations of cellular stress, including increased apoptosis, decreased vascular recovery, an aberrant inflammatory response, and delayed cellular turnover in diabetic wounds, resulting in impaired wound healing [1,10,24,25]. Although previous studies have indicated various causes for impaired wound healing in diabetes, AGE have been recognized as major factors in the pathogenesis of impaired wound healing in diabetes.…”
Section: Discussionmentioning
confidence: 98%